Nível de solidão e seus fatores associados em pacientes com doença renal crônica em tratamento hemodialítico - Pallone, Joice Marques (2021)
Chronic Kidney Disease (CKD) is considered a worldwide public health problem and has a high morbidity and mortality rate. The disease exposes patients to a series of adjustments in their lives and their families, involving socioeconomic, physical, and psychological aspects. The absence from the school or work environment also characterizes the disease as a social problem, and in this way, social support and family functionality boost the well-being and health of patients based on the frequency or quantity of social relationships, performing important functions of an affective, educational, and socialization nature for the individual. The possible absence of this support network, along with dependence in performing activities of daily living, predisposes to possible negative outcomes, such as loneliness and depressive symptoms during the period of hemodialysis treatment. Objective: Verify the level of loneliness and its relationship with socioeconomic and health conditions, social support, family functionality and depressive symptoms in patients undergoing hemodialysis. Method: Analysis of secondary data, with a primary cross-sectional investigation, correlational with a quantitative approach, carried out in 2019, with 80 patients with CKD on hemodialysis. Applied instruments: socio-demographic, economic and health condition characterization, UCLA Loneliness Scale, Medical Outcomes Study Social Support Scale, Patient Health Questionnaire 9 and the Family APGAR. Results: Showed female prevalence (55%), white ethnicity (65%) and mean age 59,63years. In the perception of loneliness, the highest index was (55%), moderately high. Social support scored worst in the Positive Social Interaction domain, mean 74.31. In depression, showed prevalence of severe depression (28.7%). Family functioning showed good score (68.8%). There was a weak negative correlation between loneliness and all domains of Social Support, besides Family Functioning.